Evaluación de la factibilidad técnica de la implementación de La inyección de biosurfactantes en el campo Yariguí Cantagallo de Ecopetrol S.A. mediante simulación numérica (2017)
Evaluate the injection of biosurfactants as an Enhanced oil recovery method that possess emulsifying properties, low toxicity and biodegradability and they have been used to reduce the interfacial tension between crude oil and water in order to reduce residual oil saturation and increase hydrocarbon production.